Genetic architecture of yield contributing traits in linseed (Linum usitatissimum L.): GENETIC ARCHITECTURE OF YIELD CONTRIBUTING TRAITS IN LINSEED - NALINI TEWARI; ACHILA SINGH (Journal of Oilseeds Research, 2014)
Fifty two accessions of linseed were evaluated during rabi 2009-10 and 2010-11 to know the genetic variability, direct and indirect contribution of some metric traits on seed yield under Randomized Block Design. The results revealed that high heritability along with high genetic advance as per cent of mean was observed for number of capsules/plant, seed yield/plant and number of secondary branches/plant while high heritability coupled with low genetic advance was noticed for days to maturity and days to 50 per cent flowering. Seed yield was significant and positively correlated with number of capsules/plant, 1000-seed weight and number of secondary branches/plant. Path coefficient analysis indicated that number of capsules/plant and 1000-seed weight showed positive direct effect on seed yield/plant. These traits having positive direct effect on seed yield can be considered as a suitable selection criteria for evolving high yielding linseed genotypes.